Evaluation of specific lncRNAs, miRNAs, and mRNAs in different groups of prostate cancer - Gelareh Vahabzadeh; Amirreza Pashapour-Yeganeh; Maryam Eini; Morad Roudbaraki; Ebrahim Esmati; Amirhoushang Poorkhani; Solmaz Khalighfard; Ali Mohammad Alizadeh (BioImpacts)
Introduction: LncRNAs interact with miRNAs and mRNAs that can have a special expression pattern in a specific cell type. We investigated the specific lncRNAs, miRNAs, and mRNAs in different groups of prostate cancer (PC). Methods: The mRNAs with significant expression differences were first analyzed using the GEO and TCGA databases. The lncRNAs and miRNAs were then identified in the miRWalk2, miRmap, OncomiR, miRGator 3.0, miRCancerDB, LncRNA2target, TANRIC, LncRNADisease, Lnc2Cancer v3.0, and LncBase. Seventy subjects, including sixty PC patients classified as local, locally advanced, biochemical relapse, metastatic, and benign groups, as well as ten normal individuals, were then included. Finally, real-time PCR determined the expression of the candidate biomarkers. Results: The bioinformatics analysis detected candidate 6 miRNAs, 6 lncRNAs, and 6 mRNAs in different groups of PC patients. Unlike the significant decrease in candidate tumor suppressors, the expression levels of specific onco-lncRNA, onco-miRNA, and oncogenes exhibited a substantial increase in different groups of the patients compared to the normal group. The expression of lncRNAs, including LINC01128 (P=0.0182), LINC02246 (P<0.0001), and LINC02288 (P<0.0001), LINC00857 (P<0.0001), GNAS-AS1 (P<0.0001), and LINC02371 (P<0.0001), the expression of miRNAs, including miR-217 (P<0.0001), miR-375 (P<0.0001), miR-203a (P<0.0001), miR-876 (P=0.0046), miR-27b (P<0.0001), and miR-152 (P<0.0001), and the expression of oncogenes, including ST14 (P<0.0001), CD24 (P<0.0001), CDH1 (P<0.0001), DSC2 (P<0.0001), TGFB3 (P<0.0001), and MYL2 (P=0.0186) had significant changes at different groups of PC patients. Conclusion: Our results identified promising biomarkers that play a role in specific groups of prostate cancer patients. Detecting specific biomarkers may be an effective strategy for different groups of PC patients.